Foreign direct investment in Peru and its implications on economic growth 2009-2015 - Bustamante Romaní, Rafael (2017)
The Peruvian economy has been showing steady economic growth that has continuously extended for more than two decades, despite showing some episodes of slowdown in the wake of the latest crisis in international financial markets. Within this context, a factor that has contributed decisively to the dynamism of domestic production has been the flow of Foreign Direct Investment (FIED), which has meant the entry of large sums of foreign capital oriented towards different sectors of our economy, favoring expansion. These capital flows have been generated by the opportunities that are offering the country, such as the possibility to obtain high rates of return with a favorable economic environment for private investment and respect for the free market. In this article seeks to explain what has been its impact on economic growth it through a model of cointegration between Gross Domestic Product (GDP) and the Flow of Foreign Direct Investment (FIED).